Comparing Internal and External User Perceptions of a National Research Funding Information System (NRFIS): A Comparative Study - Tricahyono, Dodie; Perdana, Triyoga Adi (International Journal of Science, Technology & Management, 2026)
Digital transformation in the public sector requires information systems that provide consistent and equitable services to diverse stakeholder groups. A National Research Funding Information System (NRFIS) has become a strategic digital platform for managing research funding processes end-to-end across government institutions, universities, and research organizations. While previous evaluations have examined such systems using structural models, limited attention has been given to differences in perceptions between internal stakeholders and external research stakeholders. This study compares user perceptions regarding System Quality (SY), Information Quality (IQ), Service Quality (SQ), Use (UE), User Satisfaction (US), and Net Benefits (NB) between internal and external users of NRFIS. A total of 335 respondents participated, comprising 290 external stakeholders and 45 internal stakeholders. Descriptive results show that internal users consistently reported higher perceptions across all constructs: SY (4.28 vs. 3.94), IQ (4.42 vs. 3.99), SQ (4.39 vs. 3.87), UE (4.42 vs. 3.97), US (4.47 vs. 3.98), and NB (4.56 vs. 3.95). Chi-Square tests confirm statistically significant differences across all constructs (p < 0.01). Mann–Whitney U tests further validate substantial median differences (all p < 0.001). These findings demonstrate robust perception gaps between user groups, highlighting the need for improved onboarding, training, and support mechanisms for external stakeholders. This study contributes to digital governance literature by revealing structural disparities in user experience and provides policy recommendations for enhancing inclusiveness and effectiveness of NRFIS-based research funding services.